Економіко-організаційна модель управління інноваційною діяльністю на машинобудівному підприємстві на основі логістичного підходу - Гриньов, А. В.; Кабанець, Ірина Анатоліївна (Хмельницький економічний університет, 2014)
В статті представлено етапи розробки економіко-організаційної моделі управління інноваційною діяльністю на машинобудівному підприємстві на основі логістичного підходу. Досліджено траєкторію дії та чинники ефективної економіко-організаційної моделі управління інноваційною діяльністю підприємств.

The paper describes stages of the economics and organizational model development for the logistics based control over innovations at an engineering enterprise. It studied activity directions and factors of the effective economics and organizational model of the enterprise’s innovations management. The research will improve the efficiency, reliability, clarity, flexibility in logistics planning innovation and regeneration dynamics regarding the current and projected economic conditions, and should encourage the development of theoretical and applied basics of innovation processes.
Economical and organizational management model of the logistics-based control over innovations at an engineering enterprise
Keywords: процес інноваційний; рішення управлінські; управління підприємством; management; economics model; organizational model; logistic approach